Public Participation In Legislation (Legal Comparation Studies In Indonesia, South Africa, And United State) - Gusman, Delfina; Syofyan, Yunita (Faculty of Law, Andalas University, 2023)
Community participation and the legal needs of the community are inherent in the process of forming laws. In fact, these two elements are manifestations and crystallizations of the ideal idea of ​​democracy. In a democracy, public participation is a condition sine qua non. Without public participation in the process of making laws, it will only result in authoritarian regulations and bias against the true meaning of democracy. So that it will result in the formation of laws that are not sourced from the soul and legal needs of the community (volkgeist). The method in this study uses legal research methods with a qualitative approach in the form of normative legal studies and (normative legal studies), where the type of research is descriptive analytical research. In addition, the approach used is a comparative approach (comparison), a historical approach, an institutional approach and a futuristic approach. Community participation in the formation of laws in Indonesia, South Africa and the United States has already started. Although public participation in law-making has some constraints such as slowdown in the legislative process and budgetary requirements, it brings more benefits to the government and society. However, the legitimacy of the process, the issue of justice, also creates better regulations and ultimately creates a stronger quality of democracy so that there is no doubt that public participation is an important part of the legislative process.